Learners’ Perceptions of Genre-Based Pedagogy in EFL Writing - Su-Jen Lai (English Language Education Department, Universitas Majalengka, 2026)
Genre-based pedagogy, grounded in Vygotsky’s sociocultural theory, has been widely implemented in ESL/EFL contexts but remains underexplored in Taiwan and other Asian countries. This study examined Taiwanese undergraduates’ perceptions of genre-based writing instruction and its effectiveness in improving English writing proficiency. Participants consisted of three groups of students enrolled in a compulsory English Reading and Writing course offered by the Colleges of Medicine, Engineering, and Management. Using a mixed-methods design, data were collected from course materials, student questionnaires, and semi-structured interviews. Instruction focused on composing descriptive, comparison–contrast, and cause-and-effect paragraphs, with tasks contextualized to each discipline. Findings indicated that genre-based pedagogy was applied flexibly across all groups, leading to notable improvements in students’ writing performance. Participants reported increased confidence, greater awareness of genre structures, and enhanced ability to organize ideas effectively. Attitudes toward peer feedback varied by proficiency level, while teacher guidance and individual writing practice were viewed as particularly beneficial. These findings underscore the importance of adapting genre-based instruction to diverse learner profiles and proficiency levels. The study provides empirical support for the pedagogical value of genre-based writing instruction in EFL higher education, offering practical implications for curriculum design, classroom practice, and future research on genre-focused approaches in similar Asian contexts.